Comparison of Client Centered and Behaviorist Approaches in Counseling - Dwiky Fajri Al-Ghiffari; Aprilia Sari Yudha (Penerbit Hellow Pustaka, 2025)
An in-depth study of the comparison of Client-Centered and Behaviorist approaches in counseling has important significance in developing effective counseling practices. By understanding in depth these two approaches, counselors can gain a better understanding of the principles, and goals used in each approach. It is important to examine the differences between the Client-Centered approach that emphasizes empathy, understanding, and acceptance of clients as unique individuals, and the Behaviorist approach that focuses on behavioral change through measurement and reinforcement techniques. The objectives of this study are (1) to determine the concept of the client-centered approach. (2) to determine the concept of the behaviorist approach. (3) to determine the comparison of the client-centered and behaviorist approaches. Literature research was conducted by collecting information through the library, then recording and processing the data that had been obtained. The results of this study are (1) the client-centered approach is an approach that empowers clients to think for themselves, solve their own problems, and achieve self-actualization. (2) The behaviorist approach in counseling is an approach that emphasizes changing client behavior through the use of techniques based on learning principles. (3) The client-centered approach encourages counselors to create an environment that supports exploration and problem solving by clients, while the behavioristic approach involves identifying unwanted or maladaptive behaviors, as well as using structured techniques and strategies to strengthen desired behaviors and change unwanted behaviors